Mental Health Service Users Experiences of Medication Discontinuation: A Systematic Review of Qualitative Studies - Keogh, Brian; Murphy, Esther; Doyle, Louise; Higgins, Agnes; Sheaf, Greg (My University, 2022)
Background: The use of psychotropic medication is often the first line of treatment for people with mental distress. However, many service users discontinue their prescribed medication, and little is known about their experiences or the reasons why they choose to stop taking medication. Aim: The aim of this review is to synthesize research literature focused on the experiences of people who decided to discontinue taking medication for their mental health problem. Methods: A systematic review of qualitative studies was conducted. Data bases were searched for qualitative research which explored participants’ motivations for discontinuing medication and their experiences of the process. Results: Six themes were identified: (1) Taking medications: a loss of autonomy, (2) Discontinuing medication: a thought-out process, (3) Factors influencing the decision to discontinue medication, (4) Discontinuing medication: experiences of the process, (5) Outcomes of discontinuing medication, (6) Managing mental distress in the absence of medication. Conclusion: Service providers need to be aware that for some service user’s psychotropic medication is not deemed a suitable treatment approach. Those who wish to discontinue medication need to be supported in the context of positive, therapeutic risk where their mental and physical health can be monitored and the likelihood of success increased.
PUBLISHED
Keywords: Systematic review; qualitative research; medication discontinuation; service user; mental health recovery